AGGRESSIVE TAX MEASURES ON BANKING : EXPLORATION OF CORPORATE RISK AND CORPORATE GOVERNANCE - Anik Irawati; Marwana - (Proceeding International Conference on Information Technology and Business, 2018)
The aim of the study was to test empirically the aggressive tax meausers on banking: the exploration of corporate risk and corporate governance. The independent variables used in this research were the corporate risk, the number of board of directors, the independent directors and the audit committee, while the dependent variable in this study was the aggressive tax measure. The population in this study was all go public banking sector companies in the period of 2013-2015. The selection of the sample in this study used purposive sampling technique as many as 36 companies. The hypothesis was tested using multiple linear regression analysis with analysis tool SPSS version 20. The result of this study showed that the corporate risk and independent commissioners affected the aggressive tax measures. Meanwhile, the number of board of directors and the audit committee did not affect the aggressive tax measures.Keywords: Aggressive Tax, Corporate Risk, Corporate Governance, Board of Commissioners, Independent Commissioners and Audit Committee.